Morphology and identification of the pupae of several species of soil-dwelling broad-nosed weevils from Central Europe (Coleoptera, Curculionidae, Entiminae) - Gosik, Rafał; Sprick, Peter (Zootaxa, 2013)
The pupae of Otiorhynchus (Arammichnus) dieckmanni Magnano, 1979, O. (s.str.) tenebricosus (Herbst, 1784) form lugdunensis Boheman, 1843, Peritelus sphaeroides Germar, 1824, Strophosoma (Neliocarus) c.f. sus Stephens, 1831 and Tanymecus (s. str.) palliatus (Fabricius, 1787) are described and illustrated for the first time. The pupae of Barypeithes (Exomias) pellucidus (Boheman, 1834), Brachyderes (s. str.) incanus (Linnaeus, 1758), Liophloeus (s. str.) tessulatus (Müller, 1776), Phyllobius intrusus Kôno, 1948 (= Parascythopus exsulans Heijerman & Magnano, 2000) and Phyllobius (s. str.) pyri (Linnaeus, 1758) are redescribed and illustrated. Characteristic features including chaetotaxy, habitus and measurements are given. Pupae of the genera Peritelus, Strophosoma, and Tanymecus are described for the first time. Keys to the pupae of 14 genera of broad-nosed weevils, and to several species of Phyllobius and Otiorhynchus are also presented.